2021
DOI: 10.3390/ijerph18020802
|View full text |Cite
|
Sign up to set email alerts
|

Influence on Forgiveness, Character Strengths and Satisfaction with Life of a Short Mindfulness Intervention via a Spanish Smartphone Application

Abstract: Mindfulness-based interventions (MBI) are a recognized effective psychological practice characterized by attention control, awareness, acceptance, non-reactivity, and non-judgmental thinking obtained through the practice of meditation. They have been shown to be useful in reducing stress and enhancing well-being in different contexts. In this research, the effectiveness of an MBI was evaluated on variables that can promote successful job performance such as mindfulness trait, positive and negative affect, forg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 67 publications
0
28
0
2
Order By: Relevance
“…It follows that mindfulness could contribute to greater life satisfaction, because it engenders appreciating the present moment and learning to let go of judgments or taking a nonjudgmental stance towards one’s own evaluations (Kabat-Zinn, 2001 ). Indeed, a mindfulness-based intervention facilitated in Spain during the COVID-19 pandemic was shown to have significantly increased life satisfaction levels among a large sample of students (Pizarro-Ruiz et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It follows that mindfulness could contribute to greater life satisfaction, because it engenders appreciating the present moment and learning to let go of judgments or taking a nonjudgmental stance towards one’s own evaluations (Kabat-Zinn, 2001 ). Indeed, a mindfulness-based intervention facilitated in Spain during the COVID-19 pandemic was shown to have significantly increased life satisfaction levels among a large sample of students (Pizarro-Ruiz et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The 6 trials 25-30 that tested standard interventions minimally adapted for mental health during COVID-19 were conducted in Oman (N = 46), 25 Malaysia (N = 61), 26 Spain (N = 164), 27 Iran (N = 150), 28 Serbia (N = 104), 29 and China (N = 104). 30 Participants were recruited via social media, 26,29 an internet survey, 25 and a university email list; 27 in 2 trials, recruitment method was not reported.…”
Section: Resultsmentioning
confidence: 99%
“…The 6 trials 25-30 that tested standard interventions minimally adapted for mental health during COVID-19 were conducted in Oman (N = 46), 25 Malaysia (N = 61), 26 Spain (N = 164), 27 Iran (N = 150), 28 Serbia (N = 104), 29 and China (N = 104). 30 Participants were recruited via social media, 26,29 an internet survey, 25 and a university email list; 27 in 2 trials, recruitment method was not reported. 28,30 Two trials tested standard cognitive behavioural therapy delivered individually (6 sessions) 25 or in groups (10 sessions) 28 ; both reported targeting mental health symptoms from COVID-19, but neither described COVID-19-specific intervention adaptations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations